Co-Binding of Methotrexate and Cyclophosphamide via Folic Acid-Decorated Graphene Oxide Nanomaterials for Therapeutic Approach against Breast Cancer - Yanikoglu, Reyhan; Karakas, Canan Yagmur; Akin Insel, Mert; Sevgi, Merve; Caglar, Esmahan; Abdioglu, Hasan Berkay; Isik, Yagmur; Calik, Hilal; Zaman, Ali Can; Ciftci, Fatih; Cakir, Rabia; Uvet, Huseyin; et al. (WILEY-V C H VERLAG GMBH, 2025)
In this study, we developed a graphene oxide (GO)-based nanocarrier system co-loaded with methotrexate (MTX) and cyclophosphamide (CP) and functionalized with folic acid (FA) for targeted drug delivery. The synthesized CP/MTX/FA/GO system and its individual components were characterized by zeta potential analysis, FTIR spectroscopy, FE-SEM imaging, and DSC analysis. Structural characterization revealed that the 3D morphology of the CP/MTX/FA/GO formulation was denser compared to CP/FA/GO and MTX/FA/GO systems. FTIR and DSC results confirmed the successful oxidation of graphite and the physicochemical incorporation of CP, MTX, and FA into the GO structure through functional groups such as carboxylic, hydroxyl, epoxide, and carbonyl. In vitro release studies using Franz diffusion demonstrated that the drug release profile followed the Higuchi model with a high correlation coefficient (R2 = 0.9837), indicating that the release was primarily governed by Fickian diffusion, where drug transport occurs along a concentration gradient through the GO matrix. Stiffness analysis indicated that FA functionalization enhanced cell targeting and facilitated drug internalization. Cytotoxicity assays showed that CP/MTX/FA/GO exerted a significantly higher antiproliferative effect on MDA-MB-231 breast cancer cells compared to free MTX, free CP, CP/FA/GO, and MTX/FA/GO. Collectively, these findings suggest that the CP/MTX/FA/GO nanocarrier exhibits strong potential for dual-drug targeted therapy, offering synergistic cytotoxic effects and efficient drug delivery.
Keywords: Cancer therapy; Carbon materials; Cyclophosphamide; Drug delivery; Methotrexate; DRUG-DELIVERY; TARGETED DELIVERY; CELLULAR UPTAKE; GRAPHITE OXIDE; NANOPARTICLES; CELLS; SIZE; NANOCARRIER; STATISTICS; Chemistry